2021
DOI: 10.1101/2021.11.29.470309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic architecture and genomic prediction accuracy of apple quantitative traits across environments

Abstract: Implementation of genomic tools is desirable to increase the efficiency of apple breeding. The apple reference population (apple REFPOP) proved useful for rediscovering loci, estimating genomic prediction accuracy, and studying genotype by environment interactions (G×E). Here we show contrasting genetic architecture and genomic prediction accuracies for 30 quantitative traits across up to six European locations using the apple REFPOP. A total of 59 stable and 277 location-specific associations were found using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 80 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Second, if some alleles linked to the desired trait are in low frequency in one population and segregate in the other population, using only the population with the low-frequency alleles as the training set will lead to incorrect marker effect estimations. For example, Migicovsky et al (2021) showed that the NAC18.1 gene marker, which is linked to harvest date and fruit firmness, is homozygous for the favorable allele in the nine most marketed varieties in the United States, and several marker alleles detected by GWAS in the REFPOP panel are fixed in the elite population whereas they segregate in the genetic resources ( Jung et al , 2021 ). As expected in this case, the prediction for harvest date in the hybrids when using only the elite material in the training set led to predictive abilities lower than when using both populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, if some alleles linked to the desired trait are in low frequency in one population and segregate in the other population, using only the population with the low-frequency alleles as the training set will lead to incorrect marker effect estimations. For example, Migicovsky et al (2021) showed that the NAC18.1 gene marker, which is linked to harvest date and fruit firmness, is homozygous for the favorable allele in the nine most marketed varieties in the United States, and several marker alleles detected by GWAS in the REFPOP panel are fixed in the elite population whereas they segregate in the genetic resources ( Jung et al , 2021 ). As expected in this case, the prediction for harvest date in the hybrids when using only the elite material in the training set led to predictive abilities lower than when using both populations.…”
Section: Discussionmentioning
confidence: 99%
“…As expected in this case, the prediction for harvest date in the hybrids when using only the elite material in the training set led to predictive abilities lower than when using both populations. Another such example would be the Rvi6 gene that confers resistance to apple scab and all QTLs in the associated introgressed segment: the favorable allele at Rvi6 segregates in elite material ( Jung et al 2021 ) but is absent in old varieties, because the gene introgression from the wild relative M. floribunda is recent ( Gessler and Pertot 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation